Przywództwo w dążeniu do doskonałości w zarządzaniu środowiskowym - Brzozowski, Tomasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The biggest world companies are managed according to sustainable development principles. It means that economic, social and environmental issues are treated equivalently. It can be expected that these companies implement best practices in the protection of environment and promote the idea of environmental management. The best source of information about companies environmental activities are anual reports. The article presents an analysis of the contents from the selected environmental reports with the final aim to present the methods of environmental management system improvement practised by market leading companies. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 80-87